Drivers of demographic dividend in sub-Saharan Africa - Mesfin Mulugeta Woldegiorgis (Review of Evolutionary Political Economy, 2023)
Compared to other developing regions, Africa~has experienced a relatively late start to the demographic transition, although certain countries in the continent's north and south did. As a result, Africa is only now starting to broadly benefit from the demographic dividend. Thus, a study on the drivers of the dividend, the timing and length of the dividend, and the dividend optimization strategies is crucial. The paper uses a cross-country panel data for 34 African countries for the years between 1990 and 2018. To identify the drivers of the demographic dividend, fixed effects econometric analysis is used. The foremost contribution of the paper is that it empirically shows the ongoing demographic transition and the simulated time span of the potential first and second demographic dividends. It also identifies pertinent drivers of the demographic dividend. Besides, as a new conceptual framework, it introduces an innovative analytical framework for augmenting the demographic dividend from formal~migration. The framework is named after the "International Surplus Labour Circulation (ISLC) model."
Keywords: J00; J10; J18; 320; Demographic transition; Migration; Surplus labour; Surplus labour circulation